Battling self-esteem issues during SNS use: A multilevel latent variable path analysis approach - KHOO, Shi Ann Shuna (Institutional Knowledge at Singapore Management University, 2022)
Although studies have consistently indicated that heavier social networking sites (SNS) use perpetuates poorer self‑esteem outcomes, no study has examined potential intervention methods that can counteract the ill-effects of SNS use. We sought to examine whether SNS use in a self-affirmative manner could mitigate threats to self that are often experienced during its use. Specifically, we hypothesized that the viewing of one’s SNS profile (i.e., Instagram profile) would have self-affirmative effects on individuals and improve their self-perception, and these effects are mediated by self‑concept clarity. We tested these hypotheses through cross-sectional (Study 1) and intensive longitudinal (Study 2) studies. Across two studies, we found that participants who spent time on their own Instagram profile felt more positive about themselves. In Study 2, using multilevel latent variable path analyses, we found that SNS-influenced self‑concept clarity mediated the relations between self-affirmative SNS use and SNS-influenced self-esteem. Our findings provide preliminary evidence for our hypothesis that guided SNS use can have beneficial effects on one’s self-perception.